2019
DOI: 10.1186/s13072-018-0246-5
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt1 is essential for egg production and embryo viability in the large milkweed bug, Oncopeltus fasciatus

Abstract: BackgroundThe function of cytosine (DNA) methylation in insects remains inconclusive due to a lack of mutant and/or genetic studies.ResultsHere, we provide evidence for the functional role of the maintenance DNA methyltransferase 1 (Dnmt1) in an insect using experimental manipulation. Through RNA interference (RNAi), we successfully posttranscriptionally knocked down Dnmt1 in ovarian tissue of the hemipteran Oncopeltus fasciatus (the large milkweed bug). Individuals depleted for Dnmt1, and subsequently DNA met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
165
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(192 citation statements)
references
References 75 publications
24
165
1
2
Order By: Relevance
“…This supports the idea in Bewick et al. () that methylation may not directly influence caste determination. However, the differentially methylated gene list obtained for A. mellifera used queen samples to represent the reproductive caste (Lyko et al.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This supports the idea in Bewick et al. () that methylation may not directly influence caste determination. However, the differentially methylated gene list obtained for A. mellifera used queen samples to represent the reproductive caste (Lyko et al.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research using the milkweed bug ( Oncopeltus fasciatus ) found knocking down Dnmt1 , the gene responsible for DNA methylation maintenance, in ovary tissue with RNAi had no effect on gene expression, however these individuals could no longer reproduce (Bewick et al. ). This suggests methylation may play an alternative role, rather than direct regulation of gene expression, in reproduction of some insects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations